Strategies and Challenges of Religious Moderation in Sustaining Social Harmony Amid Globalization - Nurkholish, Muhammad; Faqih, Nasuka (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
This article discusses the importance of religious moderation as a strategy for building and maintaining social harmony amidst the increasingly complex dynamics of globalization. Globalization opens up space for cross-cultural and interfaith interaction, but it also increases the potential for conflict due to differences in perspectives and identities. This study employs a qualitative-descriptive approach with library research as the main method. Data were collected through a review of various relevant literature sources, including scholarly journal articles, books, policy documents, and religious texts related to issues of religious moderation, pluralism, and social harmony. The analysis focuses on the challenges, strategies, and effective implementation of religious moderation in the era of globalization. The findings indicate that religious moderation plays a vital role in mitigating potential conflicts, strengthening shared values, and shaping an inclusive and respectful society. Key strategies identified include the roles of religious and community leaders, inclusive education, interfaith dialogue, government policy support, and the use of digital media as a means to disseminate values of tolerance. The study also finds that obstacles such as fanaticism, radicalism, and the influence of extreme ideologies pose significant challenges to the implementation of religious moderation. Through a comprehensive and collaborative approach, religious moderation can serve as a crucial pillar in strengthening social cohesion in multicultural societies in this global era.